Proposal to implement hoshin kanri at the health environment - Mendes, Fredjoger (Journal of Innovation and Healthcare Management, 2019)
The lean approach has been applied on different environments beyond manufacturing, as on healthcare, however it is still noticeable that most part of the papers refers to operational tools applications, what does not guarantee that lean thinking would be sustainable neither perennial on the organization. This paper aims to propose an implementation model that minimizes the risks through the initial process and assure the system is maintained independently of the health organizations’ size and its specialized actuation processes by involving top management on the lean approach and structure it to be deployed, followed up and reviewed continuously.